William-the outlaw. - Crompton,Richmal (London: Macmillan children book, 1999)
William and the Outlaws are back and up to no good. In this collection of ten stories, a long-awaited visitor arrives and wants to send William away to boarding school! Luckily, William the noisy, wild and muddy Outlaw always has something up his sleeve. He's not about to let that happen.
Keywords: English-Fiction